2017
DOI: 10.17532/jhsci.2017.420
|View full text |Cite
|
Sign up to set email alerts
|

Self-care behaviors and practices of nursing students: Review of literature

Abstract: Self-care is a vital component of nursing practice and is essential for the well-being of human beings, that is, both patients and nurses. However, nurses and nursing students tend to focus more on self-care of their patients and often pay little or no attention to personal self-care. This literature review explored self-care behaviors and practices of nursing students in general as well as across academic years of the study. In total, 11 studies were reviewed and critically appraised to identify current trend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…It was found that female nurses were more involved in mindful self-care than their male counterparts. Inconsistent with this finding, Younas (2017b) after a review of 11 studies on self-care behaviors and practices of nursing students noted that there is limited evidence to support any difference in the self-care behaviors and practices of male and female nursing students. On the other hand, Ahmadi et al (2019) found no difference in male and female nurses’ self-care behaviors.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…It was found that female nurses were more involved in mindful self-care than their male counterparts. Inconsistent with this finding, Younas (2017b) after a review of 11 studies on self-care behaviors and practices of nursing students noted that there is limited evidence to support any difference in the self-care behaviors and practices of male and female nursing students. On the other hand, Ahmadi et al (2019) found no difference in male and female nurses’ self-care behaviors.…”
Section: Discussionmentioning
confidence: 98%
“…Despite the above-noted benefits of mindful self-care, recent research and reviews indicated that nurses and nursing students do not actively engage in physical self-care activities such as regular exercise, refraining from smoking, and healthy dietary habits (Nahm et al, 2012; Younas, 2017b). Research demonstrates that nurses have knowledge about self-care, but the knowledge is not fully translated into their practice (Ross et al, 2017).…”
Section: Research Gaps and Rationale For This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The nurses should know that performing the self-care practices deliberately and health-promoting initiatives reduces stress and improve the quality of life. They realize the importance of physical health, including maintaining their diet, adequate sleep, and physical activity to improve physical and psychological well-being [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, multiple efforts are being made to improve the health of caring professionals [ 46 , 47 ]. However, there are still few studies on nursing students’ health behaviours about self-care [ 48 , 49 , 50 ] despite the fact that these are the next generation of employees in the health system [ 51 , 52 ]. In addition, it is interesting to analyse the process, which relates self-care with the SMH during the studying years, because a powerful SOC seemingly leads to appropriate self-care [ 53 ].…”
Section: Introductionmentioning
confidence: 99%